A Shorter Duration of the Indian Summer Monsoon in Constrained Projections - Yifeng Cheng; Lu Wang; Xiaolong Chen; Tianjun Zhou; Andrew Turner (Geophysical Research Letters)
Abstract A reliable projection of the future duration of the Indian summer monsoon (ISM) provides an important input for climate adaptation in the Indian subcontinent. Nevertheless, there is low confidence for projections of ISM duration, due to large inter‐model uncertainty of onset and withdrawal changes. Here, we find that models with excessive sea surface temperature (SST) over the tropical western Pacific (WP) during spring and greater surface warming trends over the northern mid‐high latitudes (NMHL) during autumn in the present day tend to overestimate future delays to ISM onset and withdrawal, respectively. This can be attributed to the influence of surface thermal conditions on upper‐tropospheric warming patterns. Constrained by the observational WP SST and NMHL surface warming trends, projected ISM duration under a high‐emission scenario is shortened by 6 days compared to the current climate, with a reduction of inter‐model uncertainty by 46% relative to the unconstrained results.